Influence of ingaalp laser (660nm) on the healing of skin wounds in diabetic rats - Carvalho,Paulo de Tarso Camillo de (2010)
PURPOSE: To determine the influence of low-power laser (660 nm) on the collagen percentage and macrophages in skin wounds in diabetic rats. METHODS: 30 male Wistar rats were used, distributed in two groups: laser treated diabetic (n= 15); untreated diabetic (n = 15). The diabetes was induced by intravenous injection of alloxan into the dorsal vein of the penis, at a rate of 0.1 ml of solution per 100 g of body weight. A wound was made on the back of all the animals. Groups 2 were treated with Aluminium Gallium Indium Phosphide - InGaAlP type diode laser (Photon Laser III DMC®) with a continuous output power of 100 mW and wavelength (?) of 660 nm (4 J/cm²) for 24 s. five animal from each group was sacrificed on the 3rd, 7th and 14th days after wounding. Samples were taken, embedded in paraffin, stained with hematoxylin-eosin, Masson's trichrome, and immunohistochemical macrophage. morphometrically analyzed using the Image Pro Plus 4.5 software. The percentages of collagen fibers and macrophages were determined from the samples from the euthanasia animals. RESULTS: The data were treated statistically using analysis of variance (ANOVA) and the Post-hocTukey test. The significance level was set at 0.05 or 5%. CONCLUSION: The low-power laser (660 nm) was shown to be capable of influencing the collagen percentage in skin wounds by increasing the mean quantity of collagen fibers and macrophages.